Epidemiology of Community-Onset Severe Bacterial Infections in Children and Its Evolution: A Population-Based Study in France*. Issue 6 (June 2020) - Lorton, Fleur; Chalumeau, Martin; Martinot, Alain; Assathiany, Rémy; Roué, Jean-Michel; Bourgoin, Pierre; Chantreuil, Julie; Boussicault, Gérald; Gaillot, Théophile; Saulnier, Jean-Pascal; Caillon, Jocelyne; Levy, Corinne; et al.
Abstract : Objectives: To describe the epidemiology of community-onset severe bacterial infections in children and its recent evolution. Design: Prospective, observational, population-based study from 2009 to 2014. Setting: An administrative area accounting for 13% of the French pediatric population. Patients: All children 1 month to 16 years old who died before admission or were admitted to a PICU for a community-onset severe bacterial infection. Interventions: None. Measurements and Main Results: The incidence and mortality rate of community-onset severe bacterial infections were compared with data from a reference population-based study conducted between 2000 and 2006, that is, before national recommendations for antimeningococcal C and antipneumococcal generalized vaccinations. Among the 261 children included (median age 25 mo), 28 (10.7%) died. The main diagnoses were meningitis ( n = 85; 32%) and purpura fulminans ( n = 59; 22%). The most common isolated bacteria were Neisseria meningitidis ( n = 75; 29%), including 47 (63%) cases of serogroup B and 15 (20%) serogroup C, Streptococcus pneumoniae ( n = 49, 19%), and Staphylococcus aureus ( n = 15; 6%). The incidence of community-onset severe bacterial infections was three per 100, 000 person-years (95% CI, 2.6–3.3) and had decreased by 53% from the reference period. Mortality rate was 0.3 per 100, 000 person-years (95% CI, 0.2–0.4) and had decreased by 73% from the reference period. The incidence of community-onset severe bacterial infections caused by N. meningitidis and S. pneumoniae was 0.8 and 0.5 per 100, 000 person-years and had decreased by 70% and 67% from the reference period. The incidence of community-onset severe bacterial infections–related to Staphylococcus aureus was 0.16 per 100, 000 person-years and had increased by 220% from the reference period. Conclusions: The incidence and mortality rate of community-onset severe bacterial infections, except for S. aureus infection, have decreased in France. N. meningitidis and S. pneumoniae continue to account for many infections, which indicates the need for better vaccination coverage and spectrum. Abstract : Supplemental Digital Content is available in the text.